Peran Perempuan dalam Pembangunan Ekonomi Pertanian - Hilmy Awalu Faizien (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study aims to comprehensively examine the role of women in agricultural economic development through three main focuses: women's real contribution in agricultural economic activities, structural and socio-cultural barriers that limit their participation, and empowerment strategies to realize a more inclusive agricultural economy. The background of this research stems from the reality that although women play a significant role in various aspects of agricultural production and resource management, recognition of their contribution is still structurally and culturally limited. This research uses a descriptive qualitative method with a library research approach, which utilizes primary sources such as official government documents and reports of international institutions, as well as secondary sources in the form of relevant scientific literature. Data were collected through a systematic search of digital databases, then analyzed using content analysis techniques to identify key themes related to the roles, barriers and strategies for empowering women in the agricultural economy. The results show that women have concrete contributions in production activities, processing of agricultural products, and financial management of farm-based households. However, their participation is still hampered by patriarchal structures, limited access to resources (such as land, capital, and training), and social norms that tend to marginalize women's role in decision-making. Effective empowerment strategies include strengthening women's capacity through education and skills training, forming women's farmer groups, and advocating for policies that support gender equality in agricultural development. In conclusion, the role of women in the agricultural economy is not only relevant but also crucial in promoting food security and sustainable rural development. Therefore, the integration of gender perspectives in agricultural policy is an urgency that cannot be ignored.